Goochem in mokum, wisdom in Amsterdam : papers on biblical and related wisdom read at the fifteenth joint meeting of the Society of Old Testament study and the Oudtestamentisch Werkgezelschap, Amsterdam, July 2012 - Brooke, George J.; Hecke, P. van (Oudtestamentische Studiën, Old Testament Studies, 2016)
This collection of essays is focused on the wisdom traditions of the Hebrew Bible, including the Book of Sira . The Biblical books are read as literary works on their own as well as in an Ancient Near Eastern setting. Some essays scrutinize Greek and Hellenistic wisdom traditions. The authors refrain from a definition of 'wisdom' which would have been a reductionist exercise in view of the great variety of material and the complexity of the perennial problems (wo)mankind is confronted with.